Optimisation of assembly scheduling in VCIM systems using genetic algorithm - Son Duy Dao; Kazem Abhary; Romeo Marian (Journal of Industrial Engineering International, 2017)
Assembly plays an important role in any production system as it constitutes a significant portion of the lead time and cost of a product. Virtual computer-integrated manufacturing (VCIM) system is a modern production system being conceptually developed to extend the application of traditional computer-integrated manufacturing (CIM) system to global level. Assembly scheduling in VCIM systems is quite different from one in traditional production systems because of the difference in the working principles of the two systems. In this article, the assembly scheduling problem in VCIM systems is modeled and then an integrated approach based on genetic algorithm (GA) is proposed to search for a global optimised solution to the problem. Because of dynamic nature of the scheduling problem, a novel GA with unique chromosome representation and modified genetic operations is developed herein. Robustness of the proposed approach is verified by a numerical example.
Keywords: 650; Optimisation; Assembly scheduling; Hard precedence constraint; Virtual computer-integrated manufacturing